Central Vascular Complications Following Elective Catheterization Using Transradial Percutaneous Coronary Intervention. (March 2017) - Merkle, Julia; Hohmann, Christopher; Sabashnikov, Anton; Wahlers, Thorsten; Wippermann, Jens
Percutaneous coronary intervention is commonly used to treat coronary artery disease. Both transradial and transfemoral approaches are applied. In general, fewer complications are seen with the transradial approach compared to the transfemoral access, for which reason the transradial catheterization is frequently preferred. In this case presentation, we describe 2 cases of elective transradial coronary angiography both resulting in severe central vascular complications: perforation of the right subclavian artery with a mediastinal hematoma and dissection of the brachio-cephalic trunk and the aortic arch. Although the transradial access is generally considered safe, severe complications such as artery dissection or perforation can occur even in cases of elective procedures.